Thicker Ice Improves the Integrity and Angular Distribution of CDC48A Hexamers on Cryo-EM Grids - Huntington, Brandon; Zhao, Lingyun; Bron, Patrick; Shahul Hameed, Umar F.; Arold, Stefan T.; Qureshi, Bilal M. (Frontiers in Molecular Biosciences, 2022)
Many cryogenic electron microscopy (cryo-EM) single particle analyses are constrained by the sample preparation step upon which aggregation, dissociation, and/or preferential orientation of particles can be introduced. Here, we report how we solved these problems in the case of CDC48A, a hexameric AAA ATPase from Arabidopsis thaliana. CDC48A hexamers are well preserved under negative staining conditions but disassemble during grid freezing using the classical blotting method. Vitrification of grids using the blot-free Chameleon method preserved the integrity of particles but resulted in their strong preferential orientation. We then used a strategy where we improved in parallel the purification of CDC48A and the conditions for cryo-EM data acquisition. Indeed, we noted that images taken from thicker ice presented an even distribution of intact particles with random orientations, but resulted in a lower image resolution. Consequently, in our case, distribution, orientation, image resolution, and the integrity of particles were tightly correlated with ice thickness. By combining the more homogeneous and stable CDC48A hexamers resulting from our improved purification protocol with an iterative search across different ice thicknesses, we identified an intermediate thickness that retained sufficiently high-resolution structural information while maintaining a complete distribution of particle orientations. Our approach may provide a simple, fast, and generally applicable strategy to record data of sufficient quality under standard laboratory and microscope settings. This method may be of particular value when time and resources are limited.